Adaptation of the pine fungal pathogen Grosmannia clavigera to monoterpenes: Biochemical mechanisms revealed by RNA‐seq analysis. Issue 6 (31st July 2017) - Kligun, E.; Ostretsov, B.; Titievsky, A.; Farkov, M.; Alamouti, S. M.; Brodsky, L.
Summary: The blue stain fungus Grosmannia clavigera (G. clavigera) is a pathogen of pines that can tolerate monoterpenes in oleoresin. Grosmannia clavigera has developed several mechanisms to cope with the host's monoterpene defence: a monoterpene efflux system mediated by an ABC transporter and enzymes that utilize or modify monoterpenes. In this study, we integrated two expression data sets based on a match between their multi‐dimensional distributions. The data sets are raw RNA‐seq and already processed transcriptome expression data with partially matching biological conditions. As a result, several new regulatory mechanisms, including the upregulation of the stress response and the developmental process at early‐time‐point terpene treatment, were involved in the adaptation of G. clavigera to monoterpenes and were supported by both data sets. In addition, several genes related to terpenoid modification were upregulated within 36 h (in rich media) and 7 days (in poor media) of terpene treatment. These results led us to the assumption that G. clavigera used terpenes as an energy source within 7 days when no other energy source was available, while within 36 h of terpene treatment on rich media these genes took part in terpene detoxification. As the G. clavigera genome is not well annotated, we performed detection of new putative transcripts as genome fragments enriched by read mapping. Several newly detected transcripts annotated as putative retrotransposons were upregulated mostly under early‐time‐point terpene treatment, while others annotated as putative ribonuclease and protease were downregulated mostly during early‐time‐point terpene treatment. Based on these results, it can be hypothesized that these new transcripts could play a role in previously unidentified G. clavigera terpene response regulatory mechanisms. Overall, this study identified gene expression regulations supported by two data sets as well as new putative transcripts related to new processes that might be important for G. clavigera tolerance to terpenes.